THE IMPACT OF SOCIAL MEDIA FOR TEENAGERS - Intania, Iren; Rahmadani , Alini; Tri Lestari , Nina; Dwi Andika , Windi; Fatiyah, Najlatul (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study explores the impact of social media on teenagers, focusing on both its positive and negative effects. As social media platforms become integral parts of daily life, understanding their influence on adolescent development is crucial. The research highlights how social media offers opportunities for self-expression, education, and socialization, yet also contributes to mental health issues such as anxiety, depression, and body image concerns. Through a qualitative approach, data was collected from interviews and surveys with teenagers, as well as observations of their social media behaviors. The results show that while teenagers often feel a sense of belonging and connection, the pressure to maintain a curated online persona and the constant comparison with others can negatively affect their self-esteem. This study emphasizes the need for better digital literacy programs and parental guidance to help teenagers healthily navigate social media. Ultimately, the findings suggest that balancing social media use with offline activities is essential for maintaining mental well-being.